Chronic Atypical Depression as an Early Feature of Pituitary Adenoma: A Case Report and Literature Review - Filipa Cardoso; Heela Azizi; Alexander Kilpatrick; Olaniyi Olayinka; Tasmia Khan; Alexa Kahn; Cecilia Canale; Chiedozie Ojimba; Olusegun Popoola; Deepa Nuthalapati; Maleeha Ahmad; Mirna Iskander; et al. (Case Reports in Psychiatry)
Pituitary adenomas are often diagnosed as incidental findings on brain imaging. We present the case of a 52-year-old African American female patient with long standing depressed mood prior to the incidental finding of a pituitary adenoma. We explore the possibility of certain mood symptoms prompting an early diagnosis of pituitary adenoma.